An investigation of multi-roller burnishing Process on mild steel and copper metal - Omar, Badrul (2007)

(untitled)
Burnishing is a chipless machining process. It produces smooth finishing both on round and flat surfaces. It easily produces work hardened surface by plastic deformation of surface irregularities. The burnishing is carried out by pressing a freely rotating hardened ball or roller against a rotating or flat or stationery work piece. The surface roughness is produced by the planetary rotation of ball / roller. The resulting cold working process produce smooth surface roughness, induces compressive strength, resist wear, corrosion resistance and improves fatigue life of the work part. The ball burnishing improves circularity of the work pieces. The burnishing process also improves surface hardness on the work piece surface considerably. Various spindle speeds, feed and depth of penetration are used to perform the experiments. High spindle speed and feed for the same depth of penetration produced lower value in surface roughness. The surface hardness on the surface was also increased by increasing depth of penetration for given spindle rotation and feed. The surface hardness can be increased to certain value, however, there is a limitation.